Snake Venom Polypeptides Affecting the Central Nervous System - Utkin, Yu N.; Osipov, Alexey V. (Central Nervous System Agents in Medicinal Chemistry, 2007)
There are numerous evidences about the effects of crude snake venoms or isolated toxins on the peripheral nervous system. However, the data on their interactions with the central nervous system (CNS) are not so abundant, since the blood-brain barrier (BBB) impedes penetration of these compounds into the brain. There are several reviews describing the interactions of particular classes of snake venom polypeptides with components of the CNS; however, no general systematics of such interactions was done. This review is the first attempt to consolidate the data about the interaction of snake venom polypeptides with the CNS. Such data will be described according to three main modes of interactions: - Direct in vivo interaction of the CNS with venom polypeptides capable to penetrate BBB. - In vitro interactions of isolated components of the CNS with crude venoms or purified toxins. - Indirect effects of snake venoms or their components on functioning of the CNS under normal or pathological conditions. Although the venom components penetrating BBB are not numerous, they seem to be the most suitable candidates for the leads in drug design. The compounds from two other groups are more abundant and better studied, but the fact that the data about their ability to penetrate BBB are still absent may substantially aggravate the potentials for their medical perspectives. Nevertheless, many of these compounds are used as biochemical tools for research of the CNS in vitro. These investigations may give invaluable information for understanding the molecular basis of CNS diseases and thus lay the basis for targeted drug design. This aspect also will be outlined in the review.
Keywords: brain